Peyton Place - Metalious, Grace (Julian Messner, 1956)
Considered scandalous it its time of publication, Peyton Place, stirred controversy with its explicit for the time depictions of sex and sins in a small New England town. Today, the once shocking novel and its sequel seem tame, and are taught in college English courses as classics of their time, well-written and honest in the evocation of the passions, jealousies, and secrets of small-town America.
Keywords: Literature & Fiction; New England